2014
DOI: 10.4067/s0717-95022014000200034
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Characteristics of Infra-Lamina Ridge in Chinese Population

Abstract: SUMMARY:The aim of our study was to observe the occurrence rate and morphological characteristics of Infra-Lamina ridge (ILR) in Chinese population and provide a comprehensive reference for its clinical implication. Vertebrae columns of 82 sets of Chinese adult skeletons were collected. The shape of ILR was classified into three types; the occurrence of it in different sides and sexes were counted. The length, width, thickness of ILR were measured using a caliper with 0.02 mm accuracy. The ILR was usually foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Therefore, the diameter of the spinal canal has important meaning for the clinical judgment of spinal development, spinal stenosis, or pedicle screw implantation. However, the current studies are more concentrated on adults [ 15 ], and a certain Chinese researcher [ 16 ], who observed 100 cases of adult lumbar spinal specimens, concluded that the spinal ID in both men and women showed an increasing trend with the increasing vertebral sequence. Some foreign scholars reported [ 17 , 18 ] that the overall trends were similar, but different races had different spinal IDs, which might be related to ethnicities, geographies, or sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the diameter of the spinal canal has important meaning for the clinical judgment of spinal development, spinal stenosis, or pedicle screw implantation. However, the current studies are more concentrated on adults [ 15 ], and a certain Chinese researcher [ 16 ], who observed 100 cases of adult lumbar spinal specimens, concluded that the spinal ID in both men and women showed an increasing trend with the increasing vertebral sequence. Some foreign scholars reported [ 17 , 18 ] that the overall trends were similar, but different races had different spinal IDs, which might be related to ethnicities, geographies, or sexes.…”
Section: Discussionmentioning
confidence: 99%